PERILAKU ORGANISASI DALAM PENINGKATAN KUALITAS KERJA BIROKRASI (Suatu Studi pada Direktorat Urusan Pemerintahan Daerah dan Direktorat Pengembangan Kapasitas dan Evaluasi Kinerja Daerah, Direktorat Jenderal Otonomi Daerah, Kementerian Dalam Negeri) - , NUR WAHYUNI,DRA.; , Prof. Dr. Warsito Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main purpose of this research is to study Organisational Behavior in order to Improve the Bureaucracy Working Quality in Regional Obligatory/Optional Function Directorate and Capacity Building and Regional Autonomy EvaluationDirectorate of Regional Autonomy Directorate General of Ministry of Home Affairs. This research focus on how to answer research question about how far did the Organisational Behavior Improves the Bureaucracy Working Quality Effectiveness in Regional Obligatory/Optional Function Directorate and Capacity Building and Regional Autonomy Evaluation Directorate of Regional Autonomy Directorate Jenderal of Ministry of Home Affairs.